An Analysis of the Relationship between Insurance Risk Management and Growth of the Nigerian Economy - Okoye, Nonso Fredrick; Egbo, Obiamaka; Okeke, Onuora M.; Nwankwo, Ebele (International Journal of Economics and Financial Modelling, 2017)
This study sought to examine the causal relationship between insurance risk management and growth of Nigerian economy within the period, 1981 to 2011. The study employed the Ordinary Least Squares technique in addition to, Johansen co-integration, Granger causality test, Error Correction Model (ECM), impulse response function and variance decomposition statistical methods of estimations. On the short run relationship, the study observed the existence of positive relationship between insurance risk management proxied by insurance various claims payment and the growth of Nigerian economy except the claim payment on marine policy which related negatively with growth of Nigerian economy within the period. Also, the study revealed the existence of equilibrium relationship between our employed variables and our ECM, denoting that 11% deviation from the equilibrium can be corrected over a year. On the direction of causal relationship, the study found no bidirectional relationship between our employed variables, however, a unidirectional relationship was observed from CPF to GDP, GDP to CPA, GDP to CPM, and GDP to CPMA. From our impulse response function, it was observed that GDP responded positively to own shock both in the long and short run, while its response to shocks from other variables was mixed. We found from our variance decomposition estimate that own shock represents the greatest source of variations in the forecast error of observed variable (GDP). Based on these findings, the study recommends among others that: Effort should limit the level protocols required by insurance sectors in the case of indemnification.